2013
DOI: 10.1177/0161734612472408
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Characterization of the Upper Trapezius Muscle in Patients with Chronic Neck Pain

Abstract: Myofascial trigger points (MTrPs) are palpable, tender nodules in taut bands of skeletal muscle that are painful on compression. MTrPs are characteristic findings in myofascial pain syndrome (MPS). The role of MTrPs in the pathophysiology of MPS is unknown. Localization, diagnosis, and clinical outcome measures of painful MTrPs can be improved by objectively characterizing and quantitatively measuring their properties. The goal of this study was to evaluate whether ultrasound imaging and elastography can diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 13 publications
3
62
0
4
Order By: Relevance
“…They found that the parameters were able to distinguish between healthy and pathologic muscles but not between muscles affected by different pathologic conditions. Entropy filtering, combined with vibration elastography, was used in another study on the myofascial trigger points of the upper trapezius muscle (Turo et al 2013). The combination of the two measurements lead to overall good performance (sensitivity of about 70% 9.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the parameters were able to distinguish between healthy and pathologic muscles but not between muscles affected by different pathologic conditions. Entropy filtering, combined with vibration elastography, was used in another study on the myofascial trigger points of the upper trapezius muscle (Turo et al 2013). The combination of the two measurements lead to overall good performance (sensitivity of about 70% 9.…”
Section: Discussionmentioning
confidence: 99%
“…According to their suggestion, in comparison with normal muscle, MTrPs have more heterogeneous stiffness and homogeneous texture. They emphasized the importance of evaluation of muscle tissue surrounding palpable MTrPs for better understanding of the pathophysiology of MPS [18].…”
Section: Discussionmentioning
confidence: 99%
“…Пульсовой индекс был выше в активных МТТ по сравнению с латентными МТТ и здоровыми тканями. Таким образом, можно косвенно су-дить об увеличении объема крови в сосудах, окружающих активные МТТ [19,20].…”
Section: эксперты международной ассоциации по изучению боли (Iasp 20unclassified